Effects of pretreatment with rosemary (Rosmarinus officinalis L.) in the prevention of lipid oxidation in salted tilapia fillets - Afonso, M. da Silva; SanT'Ana, L. S. [UNESP] (Blackwell Publishing, 2008)
To delay lipid oxidation during meat processing, synthetic antioxidants have been used in the food industry, but the consumers' concern over their toxicity increased interest in research with natural antioxidants. The aim of this work was to analyze the water activity (A(w)), thiobarbituric acid reactive substances (TBARS), moisture and trichloroacetic acid-soluble nitrogen (TCASN) in brined tilapia fillets treated or pretreated with natural rosemary extract (Rosmarinus officinalis) and stored for 240 days at -18C. Higher A(w) (0.900 +/- 0.010) and moisture (70.13 +/- 0.20) values were observed in the pretreated fillets. The TBARS values in the treatment (3.31 +/- 0.79) and pretreatment (3.39 +/- 0.53) were half the value of the control treatment (6.14 +/- 1.21) at 240 days. Statistical differences were observed in TCASN values in 180 (0.112 +/- 0.020) and 240 (0.132 +/- 0.017) days, with the pretreatment showing a more protective effect in protein oxidation. In this study, rosemary proved to be protective during the frozen storage, especially when its extract was used as pretreatment, before the salting process.